A possible principal function of corticosteroid signaling that is conserved in vertebrate evolution: Lessons from receptor-knockout small fish. Issue 184 (November 2018) - Sakamoto, Tatsuya; Hyodo, Susumu; Takagi, Wataru
Highlights: Constitutive GR or MR-knockout fish have been generated despite the lethal knockout mice. Brain-behavioral and visual responses may not be integrated in the CR knockouts. CR integration of behavioral and visual responses may be conserved in vertebrates. Future studies in cartilaginous fish will advance understanding of conserved and lineage-specific roles of CR. Abstract: Corticosteroid receptors are critical for homeostasis maintenance, but understanding of the principal roles of the glucocorticoid receptor (GR) and mineralocorticoid receptor (MR) throughout vertebrates is limited. Lines of constitutive GR-knockout zebrafish and MR-knockout medaka have recently been generated as the first adult-viable corticosteroid receptor-knockout animals, in contrast to the lethality of these receptor knockouts in mice. Here, we describe behavioral and physiological modifications following disruption of corticosteroid receptor function in these animal models. We suggest these data point toward a potentially conserved function of corticosteroid receptors in integrating brain-behavior and visual responses in vertebrates. Finally, we discuss how future work in cartilaginous fishes (Chondrichthyes) will further advance understanding of the unity and diversity of corticosteroid receptor function, since distinct orthologs of GR and MR derived from an ancestral corticoid receptor appear in these basal jawed vertebrates.